1986
DOI: 10.1095/biolreprod35.3.647
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Polycystic Ovarian Condition (PCO) in the Estradiol Valerate-Treated Rat

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
166
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 185 publications
(185 citation statements)
references
References 0 publications
16
166
0
3
Order By: Relevance
“…Furthermore, increased production of VIP may underlie increased ovarian capacity of EV-treated rats to produce estradiol, in the face of reduced circulating levels of FSH (reported previously; Brawer et al 1986, Rosa-e-Silva et al 2003.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, increased production of VIP may underlie increased ovarian capacity of EV-treated rats to produce estradiol, in the face of reduced circulating levels of FSH (reported previously; Brawer et al 1986, Rosa-e-Silva et al 2003.…”
Section: Discussionmentioning
confidence: 94%
“…Rats were injected with 2 mg EV on day 60G5 of postnatal life and studied 60 days later. In previous studies, we have demonstrated that this mode of treatment leads to polycystic ovarian morphology, persistent estrus condition accompanied with increased circulating estradiol levels (Brawer et al 1986, and hypersecretion of androgens and estradiol from ovaries incubated in vitro (Brawer et al 1986, Barria et al 1993, Rosa-E-Silva et al 2003. Anovulation combined with hyperandrogenism and/or polycystic ovaries are features reflective of women with poly cystic ovary syndrome (PCOS) (Rotterdam consensus 2004).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus mouse models are good and affordable choice for this purpose (9). Numerous experimental models for PCOM have been developed using EV (18). EV can produce a PCOM model in rat with interrupting in metabolic and physiologic processes (19).…”
Section: Body Weight and Fertility Ratementioning
confidence: 99%
“…Introduction Follicular cysts have been reported in many mammalian species, including cattle (Roberts 1971, Kesler & Garverick 1982, swine (Heinonen et al 1998), dogs (Arbeiter 1993, rabbits (Lopez-Bejar et al 1998), rats (Brawer et al 1986), mares (McCue & Squires 2002), sheep (Christman et al 2000), elephants (Brown et al 1999) and women (Stein & Leventhal 1935). In cattle, this condition is characterized by large (generally $25 mm in diameter) anovular structures that persist on the ovary for at least 10 days in the absence of a corpus luteum (CL) (Roberts 1971).…”
Section: Reproduction (2005) 129 737-745mentioning
confidence: 99%